Application of BASNEF Model in Analyzing Self-Treatment Behavior among Type 2 Diabetic Patients in 2014 - Siros Kabodi; Mohammad Mehdi Hazavehei; Mehrali Rahimi; Ghodratollah Roshanaei (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Self-treatment in diabetes can change blood sugar levels and cause life-threatening complications in patients. Therefore, this study aimed to assess the application of BASNEF Model in analyzing self-treatment Behavior among patients with type 2 diabetes. Materials and Methods: This cross-sectional descriptive-analytic study was conducted on patients with type II diabetes presenting to Kermanshah Diabetes Center in 2014. The patients were randomly selected and recruited. A questionnaire was used to collect demographic data and measure constructs of BASNEF model. Data were analyzed in SPSS-16 using Mann-Whitney, Kruskal-Wallis Chi-square and logistic regression tests. Results: Of the participants, 50.5% possessed self-treatment behaviors. According to the results, BASNEF model explained 24 percent of the variance in frequency of self-treatment behaviors. Attitudes, subjective norms, and enabling factors were the most significant predictors (P<0.05). Conclusions: In this study, the prevalence of self-treatment was high among type 2 diabetic patients. Applying BASNEF model appears to be an efficient tool for predicting self-treatment behaviors among diabetic patients